The Influence Of Product Quality, Price, Location And Service Quality On Purchasing Decisions At Matahari Department Bengkulu Store - Tiken Ahiriansyah; Suwarni Suwarni; Yudi Irawan Abi (Penerbit Jurnal Indonesia, 2023)
Factors influencing consumer purchasing decisions are product quality, price, location and service quality. Consumers will tend to choose outlets that have excellent service. The research aims to determine product quality, price, location and dominant place/location influencing purchasing decisions at Matahari Department Store Bengkulu. The sample in this study was 70 customers of Matahari Department Store Bengkulu. Data collection uses instruments in the form of questionnaires and the analysis methods used are multiple linear regression, determination tests and hypothesis tests. The results of the multiple linear regression analysis obtained are as follows: Y= 9.747 + 0.897 X1 + 0.832 X2 + 0.829 X3 + 0.802 Product Variable (X1), shows t count of 2.954 > t table 1.66140 with a significance level of 0.004 < 0.050. So it can be concluded that the Product variable has a positive and significant effect on Purchasing Decisions. Price influences purchasing decisions. The price variable (X2), shows t count of 2.525 > t table 1.66140 with a significance level of 0.014 < 0.050. So it can be concluded that the price variable has a positive and significant effect on purchasing decisions. Location influences purchasing decisions. The location variable (X3), shows t count of 2,800 > t table 1.66140 with a significance level of 0.000 < 0.050. So it can be concluded that the service quality variable has a positive and significant effect on purchasing decisions. Location influences purchasing decisions. The place/location variable (X4), shows t count of 2.125 > t table 1.66140 with a significance level of 0.000 < 0.050. So it can be concluded that the service quality variable has a positive and significant effect on purchasing decisions.